Mucin-producing urothelial-type adenocarcinoma of the prostate with a gene mutation characteristic of intestinal adenocarcinoma: case report and literature review - Yu, Ao; Su, Hongbo; Yu, Peiling; Cai, Siqi; Mu, Shuaixian; Yu, Jinhui; Lu, Qianting; Miao, Yuan; Li, Ailin (Frontiers in Medicine, 2025)
We report an elderly male with mucin-producing urothelial-type adenocarcinoma of the prostate (MPUAP) and oligometastatic lung involvement, initially diagnosed as benign prostatic hyperplasia and treated with transurethral plasma resection of the prostate (TURP). Postoperative pathology indicated mucinous adenocarcinoma, with immunohistochemistry positive for CK7, CK20, and CDX-2. Next-generation sequencing (NGS) identified genetic alterations similar to those found in intestinal adenocarcinoma. After ruling out gastrointestinal and bladder tumors, MPUAP was confirmed. Ablation therapy was performed for the lung metastasis, followed by radical prostate chemoradiotherapy. Post chemoradiotherapy, the patient received XELOX + Bevacizumab regmien but switched to capecitabine monotherapy due to adverse effects. At a 12-month follow-up post-radiotherapy, no prostate recurrence was observed, though previous lung nodule ablation suggested recurrence. By reviewing historical cases, we discussed the role and significance of radical resection and TURP in MPUAP. NGS is recommended for patients with MPUAP, and regarding chemotherapy, treatment options for colorectal cancer are worth considering.